Comparing &Evaluating the Effect of Air-Powder Polishing System on the Hot Cure Acrylic Denture Base Material Cured by Different Methods - Lateef E Al-Jorani; Sundus Ismail Al-Azzawi; Ihab Nafea Yaseen (College of Pharmacy / Mustansiriyah University, 2015)
This study was designed to evaluate the effects of an air-powder polishing system on the hot cure acrylic denture base material, which was cured in the water bath and microwave method, and comparing it with a conventional dental lathe polishing specimens. Thirty samples were made from the hot cure acrylic resin denture base after being cured in water bath and microwave oven; all samples are condition and then polished. The samples were numbered and divided into two groups (according to the types of curing method), each group consists of 15 specimens and sub divided into three subgroups: airflow polishing in (30 sec.), airflow polishing in (10 sec.) and conventional dental lathe polishing in (2 min.). The average surface roughnesses of the samples have been determined with using the profilometer (surface roughness tester) before and after polishing procedures. All samples were weighted by using the precision electronic balance before and after polishing procedures to obtain the results. The statistical analysis of the results  before polishing procedures showed that there were no statistically significant difference in the surface roughness and weight loss of the hot cure acrylic denture base material for both curing  methods, while after polishing treatment by conventional dental lathe polishing (2 min.) and air-powder polishing (10 sec. and 30 sec.), the statistical analysis of the results showed that there were a decrease in the surface roughness and weight loss of the hot cure acrylic resin in the water bath method more than in the microwave method and the best result shown with 2 minutes pumice. The weight loss of the acrylic in the (10 seconds) group polished surfaces was best for the (30 seconds) group when using an air-powder polishing system. So, it is preferred when using this polishing technique especially on the microwave cure method and the air-powder, to be used effectively to polish the acrylic denture base materials using a short period time.